2007
DOI: 10.1292/jvms.69.449
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Necrotizing Splenitis in a Slaughter Pig Infected with Arcanobacterium Species

Abstract: ABSTRACT. A 6-month-old barrow presented with lethargy, inappetence and dysstasia. At necropsy, multiple coalescing hemorrhagic foci were detected in the margins of the spleen. Gram-positive bacilli were isolated from the spleen, kidney, muscle and liver. Comparative 16S rDNA gene sequencing analysis of the isolates (TO16177) revealed that they would be the same species of unpublished Arcanobacterium species strain HJ57-14E (accession no. gi 18873551) (99.7% similarity based on a comparison of 675 bp). Histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Its 16S rDNA sequence possessed 97 % identity to Arcanobacterium hippocoleae isolated from a horse with vaginitis (Hoyles et al, 2002). To our knowledge, there are only six validated species within the genus Arcanobacterium (Ohba et al, 2007). Members of this genus have been isolated from both animal and human sources (Collins et al, 1982) and include the known pathogens Arcanobacterium pyogenes and Arcanobacterium haemolyticum, and the putative opportunistic pathogen Arcanobacterium bernardiae (Billington & Jost, 2006;Funke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Its 16S rDNA sequence possessed 97 % identity to Arcanobacterium hippocoleae isolated from a horse with vaginitis (Hoyles et al, 2002). To our knowledge, there are only six validated species within the genus Arcanobacterium (Ohba et al, 2007). Members of this genus have been isolated from both animal and human sources (Collins et al, 1982) and include the known pathogens Arcanobacterium pyogenes and Arcanobacterium haemolyticum, and the putative opportunistic pathogen Arcanobacterium bernardiae (Billington & Jost, 2006;Funke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been indicated that Arcanobacterium sp. TO16177 was associated with multiple organ failures accompanied by acute hemorrhagic necrotizing splenititis in the pig [14]. Furthermore, in the very recent past, it has been confirmed that the microorganism isolated from the urogenital tract of nine pigs with varied clinical symptoms was Arcanobacterium abortisuis, though it was unclear whether Arcanobacterium abortisuis was the exact causative agent for the symptoms [20].…”
mentioning
confidence: 93%
“…strain (TO16177) (Arcanobacterium sp. TO16177) [14] and Actinobaculum suis (former Actinomyces suis, Eubacterium suis) [9,12]. Among them Actinomyces hyovaginalis [6], Actinomyces naeslundii [16] and Actinomyces suis [21] have been reported as infective agents, which cause porcine abortion.…”
mentioning
confidence: 99%
See 2 more Smart Citations